THE LEGAL EDUCATION ON PREVENTING EARLY MARRIAGE AS AN EFFORT TO INCREASE COMMUNITY LEGAL AWARENESS - Widayati Widayati; Sri Kusriyah; Winanto Winanto; Rizky Dindah Saputri (International Journal of Law Society Services, 2021)
The state guarantees the right of everyone to form a family and continue their offspring through legal marriage, and the state also guarantees the right of children to survive, grow and develop as well as the right to protection from violence and discrimination. The Marriage Law requires the age of marriage to be 19 years. However, the marriage law does not explicitly prohibit the practice of early marriage, because the marriage law also provides dispensation facilities if the prospective bride or groom is still a minor. This causes many people to carry out underage marriages or early marriages, including in Bulusari Village, Bulakamba District, Brebes Regency. The reasons are due to pregnancy out of wedlock, economic factors, and cultural factors. The solutions offered are providing understanding to the public about marriage, increasing public legal awareness about the risks of early marriage, both social and health risks, and providing assistance to children and parents who undergo early marriage.